2017
DOI: 10.1002/open.201600124
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Synthetic Access toE- andZ-Stereodefined All-Carbon-Substituted Olefin Scaffolds: Application to Parallel Synthesis of (E)- and (Z)-Tamoxifens

Abstract: A highly substrate‐general synthesis of all‐carbon‐substituted E‐ and Z‐stereodefined olefins is performed. The method comprises two sets of parallel and stereocomplementary preparations of (E)‐ and (Z)‐α,β‐unsaturated esters involving two robust and distinctive reactions: 1) stereocomplementary enol tosylations using readily available TsCl/diamine/(LiCl) base reagents, and 2) stereoretentive Negishi cross‐coupling using the catalysts [Pd(dppe)Cl2] (for E) and [Pd(dppb)Cl2] (for Z). The present parallel approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Platform synthesis is a powerful strategy to realize the synthesis of complex molecules in a programable and diversity-oriented format. In this regard, the advances of metal catalysis have inspired tremendous efforts towards modular tetraarylethene construction starting from alkenes [11][12][13][14][15][16][17] or alkynes [18][19][20][21][22][23][24][25][26] . Nevertheless, lengthy synthetic operations, the poor functional group tolerance arising from the participation of organolithium or Grignard reagents, and the often-encountered poor regioselectivity strongly limits their practical application.…”
mentioning
confidence: 99%
“…Platform synthesis is a powerful strategy to realize the synthesis of complex molecules in a programable and diversity-oriented format. In this regard, the advances of metal catalysis have inspired tremendous efforts towards modular tetraarylethene construction starting from alkenes [11][12][13][14][15][16][17] or alkynes [18][19][20][21][22][23][24][25][26] . Nevertheless, lengthy synthetic operations, the poor functional group tolerance arising from the participation of organolithium or Grignard reagents, and the often-encountered poor regioselectivity strongly limits their practical application.…”
mentioning
confidence: 99%
“…Following the procedure for the preparation of (E)-3 a, the reaction of enol tosylate (E)-1 b (3.67 g, 10.0 mmol) using (p-Me)C 6 H 4 B(OH) 2 (1.63 g, 12.0 mmol), Pd(OAc) 2 (112 mg, 0.500 mmol), PPh 3 (262 mg, 1.00 mmol), and K 2 CO 3 (1.66 g, 12. 1,138.6,139.2,147.9,165.7;IR (neat): 3059,2953,1722,1597,1379,1298,1177,1045,804,733 [8,11] Following the procedure for the preparation of (Z)-4 c, the reaction of enol tosylate (E)-3 a (105 mg, 0.50 mmol) using PhB(OH) 2 (73 mg, 0.60 mmol), Pd(OAc) 2 (1.1 mg, 0.005 mmol), SPhos (2.0 mg, 0.005 mmol), and K 2 CO 3 (83 mg, 0.60 mmol) gave the desired product [(Z)-4 a, 112 mg, 89%, E/Z = 2 : > 98]. pale yellow oil; 1 H NMR (300 MHz, CDCl 3 ): δ = 2.05 (s, 3H), 3.43 (s, 3H), 7.29-7.44 (m, 10H); 13 C NMR (75 MHz, CDCl 3 ): δ = 22.2, 51.…”
Section: Methyl (E)-2-chloro-3-phenyl-3-(p-tolyl)acryate [(E)-3 B]mentioning
confidence: 99%
“…5, 126.8, 127.5, 128.1, 128.3, 129.1, 132.5, 137.1, 142.8, 143.9, 169.6. [8,11] Following the procedure for the preparation of (Z)-4 c, the reaction of enol tosylate (Z)-3 a (105 mg, 0.50 mmol) using PhB(OH) 2 (73 mg, 0.60 mmol), Pd(OAc) 2 (1.1 mg, 0.005 mmol), SPhos (2.0 mg, 0.005 mmol), and K 2 CO 3 (83 mg, 0.60 mmol) gave the desired product [(E)-4 a, 113 mg, 90%, E/Z = > 98 : 2]. pale yellow oil; 1 H NMR (300 MHz, CDCl 3 ): δ = 2.36 (s, 3H), 3.76 (s, 3H), 6.95-7.18 (m, 10H); 13 C NMR (75 MHz, CDCl 3 ): δ = 23.2, 51.…”
Section: Methyl (E)-2-chloro-3-phenyl-3-(p-tolyl)acryate [(E)-3 B]mentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent interest in cross-coupling reactions, directed towards medicinal and process chemistry, [18][19][20][21][22], led us to investigate a concise synthesis of novel 4-(pinacolato)borane (pin)B derivative 3 derived from N-methyl-4-bromo-2(3H)-benzothiazol-2-one (5), which could serve as a convenient substrate for Suzuki-Miyaura cross-coupling reactions ( Figure 2). A literature survey using SciFinder ® revealed that a 6-(pin)B analogue was reported as the synthetic intermediate for: (1) inhibitors of matrix metalloproteinases (MMPs) and the production of tumor necrosis factor α (TNF α) [23]; (2) treatment of inflammatory respiratory diseases [24]; (3) modulators of aldosterone synthase and/or 11-β hydroxylase [25]; and (4) inhibitors of IKKβ (IκB Kinase-β) kinase [26].…”
Section: Introductionmentioning
confidence: 99%